2020
DOI: 10.12998/wjcc.v8.i15.3291
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of tubular colonic duplication using a laparoscopic approach: A case report and review of the literature

Abstract: BACKGROUND Alimentary duplication is a rare congenital disease with a reported incidence of 1 per 4500 persons, although the exact incidence has been difficult to ascertain. According to previous reports, the most common site of duplication is the ileum, and colonic duplication is rare. Due to different types and locations of the duplication, the manifestations are varied, which makes establishing an accurate diagnosis before surgery a challenge. CASE SUMMARY A 17-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This percentage is highest in colorectal duplication than in duplication along other parts of the gastrointestinal tract. Studies have suggested that the duplicated epithelium carries a high risk of carcinogenesis [ 7 , 8 ]. Fecal matter moves more slowly through a duplicated segment, which explains the common symptoms of chronic constipation and delayed transit time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage is highest in colorectal duplication than in duplication along other parts of the gastrointestinal tract. Studies have suggested that the duplicated epithelium carries a high risk of carcinogenesis [ 7 , 8 ]. Fecal matter moves more slowly through a duplicated segment, which explains the common symptoms of chronic constipation and delayed transit time.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery was introduced in the late 20th century, but not until the turn of the century was it reported to be used for alimentary tract duplication [ 13 ]. Li et al [ 7 ] reported in their paper on all colonic duplication cases published until 2020 that laparoscopic surgery has been used in about 10% of cases from then on. The postoperative recovery was uneventful in all of those patients, who fully benefited from the advantages of laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of unified diagnostic and treatment criteria for transverse colonic repetitive malformations. 12 cases were diagnosed using abdominal multirow CT ( 12 , 13 , 15 18 , 20 24 , 26 ), 8 cases using digitized barium enema colography ( 13 , 14 , 17 – 19 , 22 , 23 , 25 ), and colonoscopy in 4 cases ( 19 , 20 , 25 , 26 ), 8 cases using US ( 13 – 16 , 18 , 20 22 ) and 2 cases using plain X-ray ( 16 , 18 ). Because the symptoms of repeat transverse colon malformations in adults are mostly nonspecific, clinical diagnosis is difficult.…”
Section: Discussionmentioning
confidence: 99%